2023
DOI: 10.1159/000530665
|View full text |Cite
|
Sign up to set email alerts
|

Leisure Activities, Genetic Risk, and Frailty: Evidence from the Chinese Adults Aged 80 Years or Older

Abstract: Introduction: About half of adults aged ≥ 80 years suffer from frailty. Exercise is considered effective in preventing frailty but may be inapplicable to adults aged ≥ 80 years due to physical limitations. As an alternative, we aimed to explore the association of leisure activities with frailty and identify potential interaction with established polygenic risk score (PRS) among adults aged ≥ 80 years. Methods: Analyses were performed in a prospective cohort study of 7471 community-living older adults aged ≥ 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…It is noteworthy that three studies [31,47,62] did not make a distinction between male and female participants. Of the entire corpus of studies, 20 [25][26][27]30,[32][33][34]37,41,45,[47][48][49][50]53,57,58,61,62] adopted a cross-sectional design, whereas the remaining 18 [29,31,35,36,[38][39][40][42][43][44]46,51,52,[54][55][56]59,60] constituted cohort studies. The detailed characteristics of the 38 studies included are systematically presented in Supplemental File S2 (Table S1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…It is noteworthy that three studies [31,47,62] did not make a distinction between male and female participants. Of the entire corpus of studies, 20 [25][26][27]30,[32][33][34]37,41,45,[47][48][49][50]53,57,58,61,62] adopted a cross-sectional design, whereas the remaining 18 [29,31,35,36,[38][39][40][42][43][44]46,51,52,[54][55][56]59,60] constituted cohort studies. The detailed characteristics of the 38 studies included are systematically presented in Supplemental File S2 (Table S1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The study by Sala et al [ 23 ] found that participation in leisure activities is extremely beneficial to older people as it can help them maintain healthy cognitive, physical, and mental health during aging. Zhou et al [ 24 ] examined the relationship between leisure activities and frailty in older people and pointed out that leisure activities can decrease the risk of frailty. In addition, many studies also pointed out that leisure activity participation has many benefits for older people, such as promoting mental health [ 25 , 26 ], health promotion [ 27 , 28 ], improving family relationships and interpersonal interactions [ 29 32 ], and increasing financial benefits [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%